2020
DOI: 10.1001/jamaoncol.2020.1271
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of First-line Radiosurgery vs Whole-Brain Radiotherapy for Small Cell Lung Cancer Brain Metastases

Abstract: IMPORTANCEAlthough stereotactic radiosurgery (SRS) is preferred for limited brain metastases from most histologies, whole-brain radiotherapy (WBRT) has remained the standard of care for patients with small cell lung cancer. Data on SRS are limited.OBJECTIVE To characterize and compare first-line SRS outcomes (without prior WBRT or prophylactic cranial irradiation) with those of first-line WBRT.DESIGN, SETTING, AND PARTICIPANTS FIRE-SCLC (First-line Radiosurgery for Small-Cell Lung Cancer) was a multicenter coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 39 publications
3
91
0
1
Order By: Relevance
“…217,218 While brain metastases arising from small-cell lung cancer have historically been treated with WBRT, an international retrospective study suggested that SRS may be suitable in some cases. 219 Some brain metastases of radioresistant primary tumors such as melanoma and renal cell carcinoma have also been shown to achieve good local control with SRS. 220 Other predictors of longer survival with SRS include younger age, good PS, and primary tumor control.…”
Section: Surgerymentioning
confidence: 99%
“…217,218 While brain metastases arising from small-cell lung cancer have historically been treated with WBRT, an international retrospective study suggested that SRS may be suitable in some cases. 219 Some brain metastases of radioresistant primary tumors such as melanoma and renal cell carcinoma have also been shown to achieve good local control with SRS. 220 Other predictors of longer survival with SRS include younger age, good PS, and primary tumor control.…”
Section: Surgerymentioning
confidence: 99%
“…Thus an additional surgery can in uence the course of the disease [28] as well as a complicated wound healing [3]. Radiosurgery and whole brain therapy are possible alternatives to surgery [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This #RadOnc #JC occurred on Twitter™ from Saturday, June 21st 8AM to Sunday, June 22nd 4PM Central Standard Time (CST) in accordance with our usual protocol. The online journal club included limited-time open-access of the publication [14] and an asynchronous online discussion followed by a live-hour to reduce barriers to participation, targeted online invitations to encourage diverse perspectives across disciplines and regions, moderation by a resident (IP) and diverse faculty (MK, RS, HS), and attendance by the study’s lead author (CR). Structured discussion topics (T1, T2, T3…) included an introduction for more general audiences then critical appraisal of the cohort study for application locally and globally by patients and providers.…”
Section: Methodsologymentioning
confidence: 99%